Chemical technology : key developments in applied chemistry, biochemistry and materials science - Guarrotxena, Nekane; Zaikov, G. E. (Gennadii Efremovich), 1935-; Haghi, A. K. (Oakville, ON : Apple Academic Press, 2015)
'This collection presents to the reader a broad spectrum of chapters in the various branches of industrial chemistry, biochemistry, and materials science which demonstrate key developments in these rapidly changing fields. This book offers a valuable overview and myriad details on current chemical processes, products, and practices. This new book: - is a collection of chapters that highlights some important areas of current interest in industrial chemistry, biochemistry, and materials science - focuses on topics with more advanced methods - emphasizes precise mathematical development and actual experimental details - analyzes theories to formulate and prove the physicochemical principles - provides an up-to-date and thorough exposition of the present state of the art of complex materials - familiarizes the reader with new aspects of the techniques used in the examination of polymers, including chemical, physico-chemical and purely physical methods of examination - describes the types of techniques now available to the chemist and technician and discusses their capabilities, limitations, and applications'--
Keywords: Chemistry, Technical; Biochemistry; Materials science